ANALISA LAJU PERTUMBUHAN IKAN LELE (CLARIAS SP) PADA PENDEDERAN III HASIL TIGA SILANGAN INDUK LELE YANG BERBEDA: Analysis Of The Growth Rate Of Catfish (Clarias Sp) In Three Different Crossing Parent Catfish Results - Delo, Nyoman; Kotta, Raismin; Kurniawati, Kurniawati; Sumahiradewi, Luh Gede (Yayasan Al-Amin Qalbu, 2023)
The purpose of this study is to find measurable how big growth of catfish obtained in units of weight ( gram ) length (m) of fish, through several parameters that is the main parameters and support parameters. The method used at this study is “experiment” method that is a research method by holding some unit test activities to view a result which indicates of the position and relationship confirms between observed variables or be explored by taking to steps perform experiments, data collection, processing and analysis of data, make conclusions and reports. The results showed that highest growth rate produced by cruciferous Sangkuriang><Masamo the amount of 727,5 gram or amount of 1036,7% with the daily growth rate average weight 8,10%/day, which have an average length 12,25 cm/tail or 104,11% with growth rate of the average daily length 2,38/day. While, growth in the average weight of the lowest produced by cruciferous Sangkuriang><Phyton the amount of 618,25 gram or 866,05% with the daily growth rate average weight 7,56 %/day which have an average length the amount of 11,5 cm/tail or 91,65 % with a growth rate of average daily length 2,17%/day